Description of ten new Lobophora species from the Bismarck Sea (Papua New Guinea). Issue 3 (1st April 2019) - Vieira, Christophe; De Clerck, Olivier; Millet, Laurent; Payri, Claude E.
SUMMARY: Sampling in the framework of the research program called 'La Planète Revisitée' in Kavieng and Madang (Papua New Guinea) brought thus far unknown diversity of the brown algal genus Lobophora to the surface. DNA‐assisted alpha taxonomy allowed identifying the presence of 16 species Lobophora from these two localities, which only share four species in common. Ten species are newly described, including four, which are only known to the Bismarck Sea. A more exhaustive sampling across the Bismarck Sea, and more largely across the Coral Triangle, will very likely unveil an even greater diversity. The present study underscores the fragmentary nature of our knowledge of macroalgal diversity in this region.